SECI process and its predictors: behavioral Intention from socio technical perspective - Mohamed Razi, Mohamed Jalaldeen; Abdul Karim, Nor Shahriza; Mohamed , Norshidah (2015)
The SECI (socialization, externalization, combination, and internalization) process is considered as root components of knowledge management. Socialization and internalization are believed to be closely linked to tacit knowledge while externalization and combination related with explicit knowledge. In this backdrop this study investigates the predictors of behavioral intention on SECI process with the aim of identifying the influencing factors of tacit and explicit knowledge activities. Trust, ICT use, performance expectancy and effort expectancy were considered as predictors in this study to reflect the socio technical nature. Data were collected from 313 executives in the Sri Lankan Telecommunication Industry using self-administered questionnaires. Data analysis was conducted using the partial least square technique by utilizing smart PLS version 2.0. The findings and its implications were discussed in the later part of the paper.